2017
DOI: 10.1093/deafed/enx021
|View full text |Cite|
|
Sign up to set email alerts
|

Mothers of Deaf Children in the 21st Century. Dynamic Positioning Between the Medical and Cultural–Linguistic Discourses

Abstract: Traditional research examining the communicational choices made by families with deaf children tends to emanate from the premise that families engage with either of the two grand discourses on deafness (i.e., the medical or cultural-linguistic perspective). This study investigated hearing mother's engagement with the educational options for their child from a dynamic, poststructural perspective. Three Flemish mothers were interviewed in-depth at the child's ages of 6, 9, 12, 18, and 24 months. The data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…One study investigated decision-making following maternal suspicion of hearing loss in low-income families attending a facility in Southern India (Merugumala, Pothula, & Cooper, 2017). Four studies specified that the children had been diagnosed through newborn hearing screening (Bruin & Nevøy, 2014;Hardonk et al, 2010;Matthijs et al, 2017;Uus et al, 2015). Last, while most studies provided some details about the child/children concerned, 17 (46%) only reported on the participants' relationship to the child, and five (16%) on the relationship to the child and hearing status of the participant, despite the views and experiences of parents themselves being the foci of the studies.…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study investigated decision-making following maternal suspicion of hearing loss in low-income families attending a facility in Southern India (Merugumala, Pothula, & Cooper, 2017). Four studies specified that the children had been diagnosed through newborn hearing screening (Bruin & Nevøy, 2014;Hardonk et al, 2010;Matthijs et al, 2017;Uus et al, 2015). Last, while most studies provided some details about the child/children concerned, 17 (46%) only reported on the participants' relationship to the child, and five (16%) on the relationship to the child and hearing status of the participant, despite the views and experiences of parents themselves being the foci of the studies.…”
Section: Participantsmentioning
confidence: 99%
“…Two studies considered parental decisionmaking regarding a bone-anchored device for their child (Graham et al, 2015;Mulla et al, 2013); three papers evaluated decisions regarding communication modality and oral bilingualism (Crowe, Fordham, et al, 2014;Crowe, McLeod, et al, 2014;Guiberson, 2013); and one investigated parent choice of cochlear implant brand (Clamp, Rotchell, Maddocks, & Robinson, 2013). One study, over a series of interviews, looked at the changing values of parents and the realities of implementing a decision (Matthijs et al, 2017). Finally, six studies compared parents who had implemented an option (e.g., CI) with those who chose not to implement the same option, and the reasons for their decision (Chang, 2017;Graham et al, 2015;Hardonk et al, 2010;Kluwin & Stewart, 2000;Okubo et al, 2008;Ramsden, Papaioannou, Gordon, James, & Papsin, 2009 ).…”
Section: Focal Decisionsmentioning
confidence: 99%
See 3 more Smart Citations